Wound Healing Activity of Gel Nanoparticles of Rhaphidophora pinnnata Leaves Extract in Male Rats - Kasmadi, Fathnur Sani; Rahman, Ave Olivia; Rahman, Havizur; Yuliawati, Yuliawati; Samudra, Agung Giri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Rhaphidophora pinnata, a plant traditionally recognized for its wound-healing properties, contains active compounds such as megastigmane glycosides and damascenone, known for their anti-inflammatory effects. To enhance efficacy and user comfort, this study focused on developing an R. pinnata leaf extract nanoparticle gel. Previous research from our group highlighted the significant wound-healing potential of a conventional R. pinnata gel. This present study aimed to evaluate the wound-healing efficacy of a novel R. pinnata nanoparticle gel in male Wistar rats, specifically investigating the impact of nanotechnology application. Nanoparticles were successfully formulated via the ionic gelation method, utilizing 0.250 g of R. pinnata extract, 0.1% chitosan, 0.2% sodium tripolyphosphate, and 0.5% Tween 80. Characterization revealed an average nanoparticle size of 165.70±42.76 nm with a zeta potential of 22.0±1.83 mV. The wound-healing efficacy was assessed across five treatment groups: a positive control (Bioplasenton®), a plain gel base (Formula 0), and nanoparticle gels at 0.5% (Formula I), 1% (Formula II), and 1.5% (Formula III) extract concentrations. Statistical analysis using one-way ANOVA (p <0.05) demonstrated a significant difference in incision wound healing across the groups. Formula III, containing 1.5% R. pinnata nanoparticle extract, exhibited the most superior wound-healing effect, achieving 100% inhibition by day 14, elevated hydroxyproline levels (59 µg/mL), and histologically confirmed excellent skin tissue repair. Formulas II and I followed in efficacy. These compelling findings underscore the significant potential of utilizing nanotechnology in the development of topical preparations for accelerated and effective wound healing.